Flue Gas Desulfurization (FGD) Wastewater Treatment Using Polybenzimidazole (PBI) Hollow Fiber (HF) Membranes - Wales, Michael Dean (Membranes (Basel), 2021)
Polybenzimidazole (PBI) hollow fiber membranes were used to treat flue gas desulfurization (FGD) wastewater (WW) from a coal fired power plant. Membranes were tested using both single salt solutions and real FGD WW. The PBI membranes showed >99% rejection for single salt solutions of NaCl, MgCl(2), CaSO(4), and CaCl(2) at approximately 2000 PPM (parts per million). The membranes also showed >97% rejection for FGD WW concentrations ranging from 6900 to 14,400 PPM total dissolved solids (TDS). The pH of the FGD WW was adjusted between 3.97–8.20, and there was an optimal pH between 5.31 and 7.80 where %rejection reached a maximum of >99%. The membranes were able to operate stably up to 50 °C, nearly doubling the water flux as compared to room temperature, and while maintaining >98% salt rejection.